1995
DOI: 10.1111/j.1476-5381.1995.tb16670.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis, tumour growth and metastasis by the NO‐releasing vasodilators, isosorbide mononitrate and dinitrate

Abstract: The effect of the nitric oxide (NO)‐producing nitrovasodilators isosorbide mononitrate (ISMN) and isosorbide dinitrate (ISDN) were assessed on (a) the in vivo model of angiogenesis of the chick chorioallantoic membrane (CAM) and (b) on the growth and metastatic properties of the Lewis Lung carcinoma (LLC) in mice Isosorbide 5‐mononitrate (ISMN) and isosorbide dinitrate (ISDN), inhibited angiogenesis in the CAM dose‐dependently. ISMN was more potent in inhibiting this process. Both compounds were capable of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 34 publications
1
56
0
2
Order By: Relevance
“…On the other side, NO-releasing agents have been shown to suppress the metastatic tumor cell behavior in various in vitro and in vivo tumor models by decreasing angiogenesis and, therefore, tumor cell invasion. [9][10][11][12][13] The anti-invasiveness and anti-metastatic properties of NO have been attributed either to inhibition of angiogenic factors such as β-FGF and TGFβ1, [9][10][11] or induction of TIMP-2 production and inhibition of p38. 13 Alternatively, NO has been proposed to interfere with the storeoperated calcium mobilization through regulation of the NO/ cGMP-mediated mechanism, 10 or it can prevent the excessive formation of oxygen radicals and peroxynitrate (ONOO -), which cause cell damage and facilitate tumor metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, NO-releasing agents have been shown to suppress the metastatic tumor cell behavior in various in vitro and in vivo tumor models by decreasing angiogenesis and, therefore, tumor cell invasion. [9][10][11][12][13] The anti-invasiveness and anti-metastatic properties of NO have been attributed either to inhibition of angiogenic factors such as β-FGF and TGFβ1, [9][10][11] or induction of TIMP-2 production and inhibition of p38. 13 Alternatively, NO has been proposed to interfere with the storeoperated calcium mobilization through regulation of the NO/ cGMP-mediated mechanism, 10 or it can prevent the excessive formation of oxygen radicals and peroxynitrate (ONOO -), which cause cell damage and facilitate tumor metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with other studies showing the inhibitory effects of NO-releasing agents in metastatic tumor cell behavior both in vitro and in vivo. [9][10][11][12][13] The challenge regarding NO donors as therapeutic agents is to deliver NO in a sustained and controlled manner. NO donors that spontaneously generate large amounts of NO, independent of iNOS induction, are activated at physiological pH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study has shown that inhalant nitrite increased angiogenesis resulting in accelerated tumor growth 102 , while another demon strated that the increased nitrite levels correlated positively with vasculo-and angiogenesis 24 . But the opposite effect was also reported, showing that NO inhibited angiogenesis and tumor growth 69 . These controversial and unclear results 34 , the fact that nitrite is still used in the meat industry 89 and the recently reported presence of nitrite and nitrosamines in many organs including brain, aorta, liver, kidney and the heart 10 suggest that nitrite may not be as dangerous as previously thought and that carefully designed epidemiologic studies of nitrite's biologic role are necessary.…”
Section: Nitrite On Demand Local But Systemically Administered No Dmentioning
confidence: 96%
“…Additional studies indicated that NO donors reduced tissue angiogenesis and tumour neovascularization (Pipili-Synetos et al, 1995;Sakkoula et al, 1997). However, opinion on the role of NO in angiogenesis has been polarized by disparate observations in the literature.…”
Section: Introductionmentioning
confidence: 99%